Inflammatory biomarkers as predictors of immune activation to different irradiated sites and short-term efficacy in advanced squamous cell esophageal carcinoma received radioimmunotherapy - Li, Mengying; Cai, Guoxin; Gao, Zhenhua; Meng, Xue; Han, Xiao (Frontiers in Oncology, 2023)
Purpose The present study aimed to compare immune activation among different irradiated sites and identify potential short-term efficacy prognostic factors in patients with advanced squamous cell esophageal carcinoma (ESCC) who received radiotherapy (RT) and immunotherapy. Patients and methods We recorded the clinical characteristics, blood cell counts, and derived blood index ratios, including neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), platelet-to-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII), at three time points (before, during, and after RT) in 121 patients with advanced ESCC who had received RT and immunotherapy. Chi-square test and univariate and multivariate logistic regression analyses were used to calculate the relationships among inflammatory biomarkers (IBs), irradiated sites, and short-term efficacy. Results Delta-IBs were calculated as (medio-IBs - pre-IBs) ÷ pre-IBs. The medians of delta-LMR, and delta-ALC were the highest, whereas the median of delta-SII was the lowest in patients with brain radiation. Treatment responses were observed within 3 months after RT or until the beginning of the next line therapy, and the disease control rate (DCR) was 75.2%. The areas under the receiver operating characteristic curve (AUCs) for delta-NLR and delta-SII were 0.723 (p = 0.001) and 0.725 (p < 0.001), respectively. Multivariate logistic regression analysis showed that the treatment lines of immunotherapy (odds ratio [OR], 4.852; 95% confidence interval [CI], 1.595-14.759; p = 0.005) and delta-SII (OR, 5.252; 95% CI, 1.048-26.320; p = 0.044) were independent indicators of short-term efficacy. Conclusion In this study, we found that RT to the brain had a stronger immune activation effect than RT to extracranial organs. We also found that earlier-line immunotherapy plus RT and a decrease in SII during RT may generate better short-term efficacy in advanced ESCC.